Management Of Character Education Strengthening Program In Building The National Soul Of Vocational School Students In Bandung City (Case Study at SMKN 9 and SMKN 13 Bandung) - Dharmawan , Dedy; Trisnamansyah, Sutaryat; Mulyasana, Dedi; fiah, Hana (CV. Inara, 2022)
In the Law on the National Education System, Government Regulations, and the Strategic Plan of the Directorate General of Secondary Education (Renstra Dirjen Dikmen) 2010-2014, it is explained that education does not only form intelligent Indonesian people, but also has personality/character (cognitive aspects, affective, and psychomotor) must be met. Strengthening the character of students from an early age will make students not only smart, but also tough and have a good attitude as the capital of life. The good and strong character of students will form a strong character and national identity so that they can compete on the global stage. Demoralization problems such as the tradition of Punk children who are far from religious norms, promiscuity, free sex and acts that deviate from religious morals are part of the lives of today's teenagers. With some of these problems, there needs to be a rescue effort in order to save the morality of teenagers, especially students who are still studying in high school / vocational school. This study aims to determine: 1) the concept of character education development, 2) character values developed, and 3) the implementation of character education development in learning activities at SMKN Bandung. The philosophical foundation used is the philosophy of constructivism education. The theoretical basis used is the management theory of George R. Terry. This study uses a qualitative research method with a case study design. Data was collected by means of in-depth interviews, participant observation and documentation. After the data is obtained then it is organized, interpreted, analyzed and then concluded. The findings in this study are: 1) the concept of national spirit character education is carried out by involving at least three main elements of education, namely: a) the existence of educational support devices which include policies, guidelines, resources, environment, facilities and infrastructure, togetherness and commitment of stakeholders. b) the intervention of the values of the character of the national spirit into the three components of education in schools which include the learning process, management, and extracurricular activities. c) there is a culture of character education in schools. 2) The values of the character of the national spirit developed at SMKN Bandung include nationalist values and respect for diversity. 3) The implementation of national character education is carried out by incorporating the values of national character into the syllabus and learning device plans. Then the syllabus and lesson plans based on Islamic and national character are implemented in the classroom learning process using the CTL (Contectual Teaching ang Learning) principle, and through extracurricular activities.